Dr. Terry Dubrow — Deep Plane Facelift — Newport Beach - Dubrow, Terry (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Terry Dubrow, practicing in Newport Beach, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003218; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; newport beach